Constructing a donor–acceptor linear-conjugation structure for heterologous perylene diimides to greatly improve the photovoltaic performance. Issue 4 (26th November 2018) - Wang, Helin; Chen, Lingcheng; Xiao, Yi
Abstract : Th-4PDI, a new donor–acceptor-type non-fullerene electron acceptor material, was designed and synthesized for high efficiency organic solar cells. Abstract : By applying the concept of an acceptor–donor–acceptor (A–D–A) structure, we have designed a new linear-conjugation perylene diimide (PDI) derivativeTh-4PDI that contains four PDI units connected at different reactive positions.Th-4PDI is constructed via a coupling reaction between two heterologous PDI dimers (2PDI ) as the acceptor parts and a thiophene as the donor unit.Th-4PDI possesses a broadened absorption spectrum in the region of 400 to 700 nm and a deep lowest unoccupied molecular orbital (LUMO) level of −4.03 eV. More importantly, the active layer films based onTh-4PDI exhibit a higher charge mobility, more balanced carrier transport and more favorable nanomorphology than those of the prototype2PDI, which are important factors for achieving high efficiency in organic solar cells (OSCs). As a result, the device based on PTB7-Th:Th-4PDI shows a high power conversion efficiency (PCE) of 7.17%, which is 3 times higher than that of2PDI . The results demonstrate that constructing A–D–A type conjugated structures based on2PDI is a feasible strategy to achieve high PCEs in OSCs and also, with a rational design, the heterologous PDI arrays could be developed into high efficiency non-fullerene electron acceptor materials.